2017
DOI: 10.3126/bjhs.v1i1.17094
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Ocular Trauma Among Children in Tertiary Eye Hospital of Nepal

Abstract: available on the PDFBirat Journal of Health Sciences 2016 1(1): 33-37

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“… 12 In the present study, early presentation within 6 hours was found in 39.25% and subconjunctival haemorrhage was the most common ocular finding which was similar to other studies. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 12 In the present study, early presentation within 6 hours was found in 39.25% and subconjunctival haemorrhage was the most common ocular finding which was similar to other studies. 13 …”
Section: Discussionmentioning
confidence: 99%